DEVELOPMENT OF ENTREPRENEURIAL CULTURE IN STUDENTS IN THE CONDITIONS OF GLOBALIZATION - Januzakova Roza Baurjan qizi; Lutfullayeva N. X. (Modern American Journals, 2026)
This article investigates how entrepreneurial culture can be developed among students in pedagogical university programs under the intensifying pressures and opportunities of globalization. Entrepreneurial culture is conceptualized not as a narrow orientation to business start-up, but as a value-based and competence-based constellation that integrates initiative, responsibility, creativity, opportunity recognition, ethical risk management, collaboration, and sustained self-development. In teacher education, this culture is strategically important because future educators shape learners’ agency, career awareness, and innovation readiness through curriculum design, classroom interaction, and assessment practices. The study proposes a pedagogical framework that aligns entrepreneurial culture formation with competency-based education, project-based learning, community-linked tasks, and reflective practices supported by digital tools. Methodologically, the research employs a mixed design combining diagnostic measurement of entrepreneurial dispositions, analysis of learning products, and qualitative reflection data collected during an intervention embedded in education courses. Findings indicate that students’ entrepreneurial culture strengthens most noticeably when learning tasks are authentic, socially meaningful, and connected to local educational challenges while using global knowledge resources. The article also identifies institutional and psychological conditions that enable sustainable change, including supportive academic climate, mentorship, feedback literacy, and opportunities for iterative experimentation. The work contributes practical guidance for pedagogical universities seeking to prepare graduates who can lead educational innovation, cultivate student agency, and translate global trends into context-sensitive educational practice.
Keywords: Entrepreneurial culture, globalization, student agency, innovation competence, opportunity recognition, pedagogical entrepreneurship, project-based learning, competency-based education, social responsibility, reflective practice, digital learning environments.